(untitled) - EKA LIAWATI, NUR (LATERNE, 2013)
This study examines the outcomes of learning reading skills using instruments true or false. Instruments are true or false test form consisted of a statement that has two possibilities: true or false (Nurgiyantoro, 1998:79). Based on the interviews had been conducted with German language teacher at SMAN 1 Waru, the ability to read German language students at SMAN 1 Waru is low and most of the students have difficulties in understanding and concludes the story in a discourse that has been given, so that the student becomes less good. Therefore, in this study using the instrument of true or false to enable the student to learn German.The formulation of the problem in this research is how the learning outcomes of reading skills class XI IPA 1 SMAN 1 Waru using instruments true or false?. While the goal of this research is to investigate the learning outcomes of reading skills class XI IPA 1 SMA Negeri 1 Waru using instruments true or false. This study used a qualitative descriptive method. The study was conducted over five sessions. Sources of research data obtained from the test results of learners in the form of pre-test and post-test. The data of this study in the form of students’ test data are then described and summarized. The results obtained results and discussion chapter learning outcomes before and after implementation using an instrument true or false, with the following description: From the value of pre-test showed that only 18.18% of the number of students who already meet KKM (Minimal mastery criteria) . While the value of post-test results showed that 94.28% of the number of students who already meet the KKM. Based on these data it can be seen that there is an increase in student learning outcomes in reading skills. From the results of these studies indicate that the instrument of true or false can be used as an evaluation instrument for teachers on reading skills in German. Keywords: Instrument true or false, the result of learning, reading skills